Attitute of Students Towards People with Disabilities - Rehman, Zia; Saleem, Laiba (Poltekkes Kemenkes Jakarta I, 2022)
Objective. To determine the attitude of students of PIPOS (Pakistan Institute of Prosthetic and Orthotics Sciences) towards people with disabilities. Methods. Cross-sectional study. Pakistan Institute of Prosthetic and Orthotic Sciences Peshawar. Duration of the study was from September 2021 to November 2021. Research strategy for this study was a cross-sectional survey in which census sampling was used and data was collected by using standard questionnaire. Data was collected in PIPOS Peshawar and calculated sample size was 68 students studying in all semesters of PIPOS Peshawar. Out of 68 students 14 students were female and 54 students were male. Results. In this research total 68 students participated in which population of the students 60(80%) had positive attitude while rest of them 8(11%) had negative attitude towards people with disabilities. Mostly all the senior students show positive attitude i.e. semester 4th shows most positive attitude 89%, semester 8th shows second most positive response 88%, semester 6th shows positive response 86% and then semester 2nd shows positive response 80%. Overall attitude of the students was positive towards people with disabilities. Conclusion. The conclusion of our study is that mostly student’s shows positive attitude 80% towards people with disabilities while 11% of students shows a little negative attitude because they don't have much interaction with patients.